Impact of Social Determinants of Health on Postoperative Health-Related Quality of Life Among Patients Undergoing Colorectal Cancer Surgery - Thongdeebut, Tanaporn; Danaidutsadeekul, Suporn; Phligbua, Warunee; Lohsiriwat, Varut (Siriraj Medical Journal, 2025)
Objective: This study aimed to investigate the predictive effects of social determinants of health—specifically financial status, neighborhood environment, body mass index, anxiety, and family support—on the health-related quality of life (HRQoL) among patients undergoing colorectal cancer (CRC) surgery. Materials and Methods: A cross-sectional study was conducted with patients who underwent elective colorectal surgery and were in the postoperative period of one month in a super-tertiary hospital in Thailand. Data were collected using questionnaires and analyzed with descriptive statistics, one-way ANOVA, Pearson correlation, and multiple regression analysis. Results: A total of 130 patients were enrolled, with 71 patients (54.6%) having fewer complications. Patients who have undergone CRC surgery had an average HRQoL score of 111.9 ± 11.9. Notably, the HRQoL after surgery was higher than before, reflecting an increase of 78.5%. The significant predictive factors of HRQoL were financial status (β = 0.56, p < 0.001), followed by anxiety (β = –0.172, p = 0.011), body mass index (β = 0.171, p = 0.008), and family support (β = 0.15, p = 0.022). Conclusion: Nurses should develop practice guidelines to promote HRQoL in postoperative CRC patients after discharge by screening financial status, body mass index, anxiety, and family support. These guidelines should serve as a framework for planning ongoing care for patients and their families once they return home, ensuring that their physical, emotional, and social needs are effectively addressed during their recovery process.